Analisis Ma’Anil Hadis Tasyabbuh dalam Batasan Qaza’ Pada Rambut Laki-Laki: Telaah Kritis terhadap Pemaknaan dan Konteks - Pratama, Ridho; Mugiyono; Nurchalidin (Jurnal Diskursus Islam, 2026)
A study of hadiths regarding tasyabbuh and the prohibition of qaza’ is relevant amid the rising trend of men’s hairstyles influenced by global popular culture. This study aims to analyze the meaning of hadiths on tasyabbuh within the context of qaza’ through the ma‘ānī al-ḥadīṡ approach by examining the text (matan), chain of transmission (sanad), historical context, and its relevance today. The method used is a qualitative approach based on library research, with the primary source being the hadith narrated by al-Bukhari, supplemented by references to classical commentaries and contemporary scholarly studies. The results of the study indicate that the hadith prohibiting qaza’ is authentic and emerged from a concrete social context as a guideline for ethical appearance. Linguistically, qaza’ means trimming part of the hair while leaving the rest, reflecting an aesthetic imbalance. Scholars classify it as makruh tanzīh, not haram, as it is not accompanied by a threat of punishment. The wisdom behind the prohibition includes neatness, preventing imitation of non-Muslims, and avoiding ostentation. In the modern context, hairstyles are no longer symbols of a specific religious identity; therefore, the interpretation of the hadith must be conducted contextually through the approaches of fiqh al-awlawiyyāt and maqāṣid al-syarī‘ah. Thus, the hadith on qaza’ is understood as a guideline for ethical appearance that emphasizes balance, simplicity, and a proportionate Muslim identity, rather than an absolute restriction on hairstyle creativity.